2014
DOI: 10.1093/brain/awu248
|View full text |Cite
|
Sign up to set email alerts
|

Altered network connectivity in frontotemporal dementia with C9orf72 hexanucleotide repeat expansion

Abstract: Hexanucleotide repeat expansion in C9orf72 represents the most common genetic cause of familial and sporadic behavioural variant frontotemporal dementia. Previous studies show that some C9orf72 carriers with behavioural variant frontotemporal dementia exhibit distinctive atrophy patterns whereas others show mild or undetectable atrophy despite severe behavioural impairment. To explore this observation, we examined intrinsic connectivity network integrity in patients with or without the C9orf72 expansion. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
195
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(224 citation statements)
references
References 68 publications
26
195
1
2
Order By: Relevance
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 65%
“…In parallel with the ROI analysis, the voxel‐wise analysis showed that certain sparse regions of lower grey matter volumes tended to associate with higher poly(GP), which included regions in the bilateral dorsolateral prefrontal, medial frontal, and lateral temporal cortices. Although higher poly(GP) levels showed a relatively weak association with lower grey matter volumes in our analyses, the regions identified include those atrophied in C9orf72‐ associated FTD patients,45, 47, 48, 49 and show reduced volume in presymptomatic C9orf72 expansion carriers 23, 36…”
Section: Discussionmentioning
confidence: 55%
“…Spells in Case 1 consisted of altered consciousness, panic, and/or stereotyped behaviours, incapacitating her for hours at a time. Given her pattern of focal atrophy, we hypothesize that these periods of altered awareness reflected perturbed thalamo-cingulo-insular oscillations normally generated by the medial pulvinar thalamus, an emerging major epicentre of C9orf72 disease (Lee et al, 2014;Rohrer et al, 2015). In past decades, this patient might have been diagnosed with socalled 'thalamic dementia', a term applied when strategic vascular or degenerative thalamic lesions produced profound multi-domain cognitive-behavioural impairment (Abbruzzese et al, 1986;Szirmai et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The most common FTD syndrome in carriers is the behavioural variant (bvFTD) (Karageorgiou and Miller, 2014), and neuroimaging studies reveal bvFTDtypical atrophy involving anterior cingulate, anterior insula, and frontal and temporal cortices, as well as less typical parietal lobe, medial thalamic, and cerebellar involvement (Mahoney et al, 2012;Sha et al, 2012;Lee et al, 2014). Some carriers with bvFTD, however, exhibit slow progression and/or minimal brain atrophy (Boeve et al, 2012;Khan et al, 2012;Suhonen et al, 2015) despite predictable changes in brain connectivity, suggesting that neuronal dysfunction or disconnection leads to clinical deficits prior to overt neurodegeneration (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In bvFTD, breakdown in this afferent system may interfere with generosity by hampering patients’ access to internal emotional cues that typically motivate prosocial behaviors. Recent findings suggest that in at least one subtype of bvFTD, those with mutations in the C9ORF72 gene, the pulvinar is an early site for neurodegeneration (Lee et al., 2014), an atrophy pattern that may help to distinguish this group from other forms of frontotemporal dementia (Bocchetta et al., 2016; Whitwell et al., 2015). …”
Section: Discussionmentioning
confidence: 99%